2016
DOI: 10.1038/srep29137
|View full text |Cite
|
Sign up to set email alerts
|

Negatively charged residues of the segment linking the enzyme and cytolysin moieties restrict the membrane-permeabilizing capacity of adenylate cyclase toxin

Abstract: The whooping cough agent, Bordetella pertussis, secretes an adenylate cyclase toxin-hemolysin (CyaA) that plays a crucial role in host respiratory tract colonization. CyaA targets CR3-expressing cells and disrupts their bactericidal functions by delivering into their cytosol an adenylate cyclase enzyme that converts intracellular ATP to cAMP. In parallel, the hydrophobic domain of CyaA forms cation-selective pores that permeabilize cell membrane. The invasive AC and pore-forming domains of CyaA are linked by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 63 publications
3
74
0
2
Order By: Relevance
“…The biologic activities of the refolded pro-CyaA and CyaA species were assessed on sheep erythrocytes by monitoring hemolytic activity and the ability of the toxins to invade cells (Supplemental Table S1). As expected, the monomeric CyaA species induced hemolysis and was able to bind to erythrocytes and translocate into the cytosol in a calcium-dependent manner, in agreement with prior studies (25,47,52,53). In contrast, the multimeric CyaA species exhibited strongly reduced hemolytic activity and was not able to translocate into erythrocytes, whereas the pro-CyaA species were totally lacking hemolytic and cell-invasion capacities ( Supplemental Table S1), which is in agreement with previous studies (55,57).…”
Section: Refolding and Functional Activities Of Cyaa And Pro-cyaasupporting
confidence: 92%
See 1 more Smart Citation
“…The biologic activities of the refolded pro-CyaA and CyaA species were assessed on sheep erythrocytes by monitoring hemolytic activity and the ability of the toxins to invade cells (Supplemental Table S1). As expected, the monomeric CyaA species induced hemolysis and was able to bind to erythrocytes and translocate into the cytosol in a calcium-dependent manner, in agreement with prior studies (25,47,52,53). In contrast, the multimeric CyaA species exhibited strongly reduced hemolytic activity and was not able to translocate into erythrocytes, whereas the pro-CyaA species were totally lacking hemolytic and cell-invasion capacities ( Supplemental Table S1), which is in agreement with previous studies (55,57).…”
Section: Refolding and Functional Activities Of Cyaa And Pro-cyaasupporting
confidence: 92%
“…CyaA is a large, multidomain protein of 1706 amino-acid residues, with AC (residues 1-364) (16), whereas the C-terminal hemolysin region (residues 365-1706) contains several domains responsible for AC membrane translocation and pore-forming activity (19)(20)(21)(22)(23)(24). The translocation region (TR; residues 365-527) is involved in AC translocation across target cell membranes (24) and membrane permeabilization (25) and exhibits features similar to membrane-active peptides (24,26,27). The hydrophobic region (HR) corresponds to residues 528-710, whereas the acylation region (AR) extends from residues 711 through 1005.…”
mentioning
confidence: 99%
“…The HP region of several RTX cytolysins including CyaA has been shown to play a key role in membrane-pore formation [8,23,27]. We previously demonstrated that two putative transmembrane helices (α2 and α3) in the CyaA-Hly domain are crucially involved in hemolytic activity [23,24,25].…”
Section: Resultsmentioning
confidence: 99%
“…However, the molecular mechanism and forces involved in the translocation of the CyaA catalytic domain across the plasma membrane have thus far remained elusive. We have previously shown that a peptide, corresponding to the C-terminus of the translocation region TR of CyaA, P454 (residues 454-484, Figure S1), exhibits membrane-active properties related to antimicrobial peptides (AMPs) 17,63 : this peptide adopts a helical conformation upon membrane interaction and induces a local destabilization of the lipid bilayer [63][64][65][66] . This property is likely essential for CyaA as deletion of the TR region (residues 384-489) encompassing the P454 segment, selectively abrogates the ability of the modified toxin to intoxicate target cells 17 .…”
Section: Introductionmentioning
confidence: 99%